2010
DOI: 10.1364/oe.18.008735
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved analysis of cavitation induced by CW lasers in absorbing liquids

Abstract: We present novel results on thermocavitation using a CW medium-power near infrared laser (lambda=975 nm) focused into a saturated copper nitrate saline solution. Due to the large absorption coefficient at the laser wavelength, the solution can be heated to its superheat limit (T(sh) approximately 270-300 degrees C). Superheated water undergoes explosive phase transition around T(sh) producing approximately half-hemispheric bubbles (gamma approximately 0.5) in close contact with the substrate. We report the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 15 publications
4
50
2
Order By: Relevance
“…As power is increased, both R max and the bubble lifetime decrease almost linearly, at least in this power range. In previous works, 30 we showed that the reduction in bubble radius scales exponentially. Although the experimental conditions are different herein, there is no physical reason why this dependence should be different.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…As power is increased, both R max and the bubble lifetime decrease almost linearly, at least in this power range. In previous works, 30 we showed that the reduction in bubble radius scales exponentially. Although the experimental conditions are different herein, there is no physical reason why this dependence should be different.…”
Section: Resultsmentioning
confidence: 74%
“…As reported before, a strong shock wave is emitted upon collapse, whose amplitude scales linearly with the bubble radius. 30 In fact, Vogel et al, 31 found that for laser-induced pulsed cavitation, up to 70%-90% of the input energy is converted into mechanical energy. Although these results are valid for pulsed illumination in pure water, acoustic losses also dominate in thermocavitation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations